Suppression of charged particle production at large transverse momentum in central Pb-Pb collisions at √ˢɴɴ=2.76 TeV - Aamodt, K.; Abrahantes Quintana, A.; Adamovã, D.; Adare, A.M.; Aggarwal, M.M.; Aglieri Rinella, G.; Agócs, A.G.; Aguilar Salazar, S.; Ahammed, Z.; Ahmad, N.; Ahmad Masoodi, A.; Ahn, S.U.; et al. (Elsevier, 2011)
Inclusive transverse momentum spectra of primary charged particles in Pb–Pb collisions at √ˢɴɴ = 2.76 TeV have been measured by the ALICE Collaboration at the LHC. The data are presented for central and peripheral collisions, corresponding to 0–5% and 70–80% of the hadronic Pb–Pb cross section. The measured charged particle spectra in |η| < 0.8 and 0.3 < Pᴛ < 20 GeV/c are compared to the expectation in pp collisions at the same √ˢɴɴ, scaled by the number of underlying nucleon–nucleon collisions. The comparison is expressed in terms of the nuclear modification factor Rᴀᴀ. The result indicates only weak medium effects (Rᴀᴀ ≈ 0.7) in peripheral collisions. In central collisions, Rᴀᴀ reaches a mínimum of about 0.14 at Pᴛ = 6–7 GeV/c and increases significantly at larger Pᴛ. The measured suppression of high- Pᴛ particles is stronger than that observed at lower collision energies, indicating that a very dense medium is formed in central Pb–Pb collisions at the LHC.
Keywords: R_{AA}; Nuclear modification factor; Pb–Pb collisions; √s_{NN} = 2.76 TeV; ALICE; LHC; https://purl.org/pe-repo/ocde/ford#1.03.03